2020
DOI: 10.1039/d0sm00339e
|View full text |Cite
|
Sign up to set email alerts
|

Translational and rotational dynamics of a self-propelled Janus probe in crowded environments

Abstract: We computationally investigate the dynamics of a self-propelled Janus probe in crowded environments. The crowding is caused by the presence of viscoelastic polymers or non- viscoelastic disconnected monomers. Our simulations...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 69 publications
4
47
0
Order By: Relevance
“…Besides this, the C v (τ) falls off sharply for lower stickiness and exhibits a negative correlation at higher stickiness (ε = 2.5) due to the trapping of the tracer particle by the grafted polymers (Fig. S7(b)) 22,39,54 .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Besides this, the C v (τ) falls off sharply for lower stickiness and exhibits a negative correlation at higher stickiness (ε = 2.5) due to the trapping of the tracer particle by the grafted polymers (Fig. S7(b)) 22,39,54 .…”
Section: Resultsmentioning
confidence: 91%
“…For example, experimental investigation of self-propelled Janus particles in viscoelastic fluid demonstrated that the rotational diffusion of the particle gets enhanced with the self-propulsion velocity 38 . Computer simulations have shown that the rotational diffusivity of a self-propelled Janus particle in the crowded environment exhibits a nonmonotonous behavior while translational diffusivity decreases monotonically with the area fraction of the crowders 39,40 . On the other hand, enhancement in translational motion of the cell and a sharp decline in rotational diffusion are observed in an experimental study of E. coli in polymeric solutions 41 .…”
Section: Introductionmentioning
confidence: 99%
“…S7(b), ESI †). 22,39,54 Fig. 4 (a) Log-log plot of hdz 2 (t)i vs. t and (b) log-linear a z (t) of the tracer particle in the polymer grafted cylindrical channel at different Pe for e = 1.5.…”
Section: Resultsmentioning
confidence: 99%
“…38 Computer simulations have shown that the rotational diffusivity of a self-propelled Janus particle in the crowded environment exhibits a nonmonotonous behavior while translational diffusivity decreases monotonically with the area fraction of the crowders. 39,40 On the other hand, enhancement in translational motion of the cell and a sharp decline in rotational diffusion are observed in an experimental study of E. coli in polymeric solutions. 41 The dynamical behavior is significantly affected by the activity, degree of confinement, steric hindrance, interactions with the medium, and architecture of the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, a number of experimental and theoretical studies have been carried out to investigate the dynamics of the self-propelled species in crowded and complex environments [17][18][19][20][21][22][23][24][25] . Recent experimental and theoretical studies reported enhanced rotation of a self-propelled Janus particle in polymer solution 6,22 . Most of the previous attempts focus on the effect of crowding on dynamics by changing the nature and density of the crowders [18][19][20]26,27 .…”
Section: Introductionmentioning
confidence: 99%